ANALYSIS OF CONCRETE PERFORMANCE UTILIZING LOCALLY SOURCED MATERIALS IN LIGHTWEIGHT PERMANENT FORMWORK SYSTEMS - Дікарев, Костянтин; Мовчан, Олександр (SWorldJournal, 2025)
The large-scale invasion of Ukraine has resulted in the destruction or severe damage of over 236,000 residential buildings, yielding more than 700,000 tons of construction debris. This situation has created an urgent need for rapid, economical, and sustai